(untitled) (Journal of Hama University, 2021)
This search aimed at identifying the difference in personal traits among a sample of superior students in Damascus Governorate, according to variables of (gender, grade, and educational level of parents). The research sample consisted of (206) superior students. They were arbitrarily selected. The researchers used the Big Five Factors of Personality that prepared by (Costa & Mcrcae, 1992) after checking its psychometric properties. The research results indicated the following: -The order of Personal Traits among superior students was as followis: (conscientiousness, openness to experiences, extraversion, agreeableness and neuroticism). -There were statistically significant differences between superior students’ mean scores in (openness to experiences and extraversion) traits according to variable of gender in favor of females, and in (neuroticism) trait in favor of males. -There were statistically significant differences between superior students’ mean scores in (openness to experiences) trait according to variable of grade in favor of the higher grade. -There were statistically significant differences between superior students’ mean scores in positive traits according to variable of educational level of parents in favor of the higher education.